PENGARUH KEPEMIMPINAN DOSEN DAN KEMAMPUAN PRAKTIKUM FISIKA DASAR TERHADAP PRESTASI BELAJAR MAHASISWA DALAM MATAKULIAH FISIKA DASAR - Tarmizi Tarmizi (Syiah Kuala University, 2015)
The purpose of this study was to calculate (1) the value of coefficient of correlation between Leadership Lecturer of the ability practicum Physics, (2) the correlation coefficient between the Leadership Lecturer on Learning Achievement in Physics (3) the correlation coefficient between the ability practicum Physics of the Learning Achievement of Physics basis, and (4) the value of multiple correlation coefficient between the leadership and the ability practicum Lecturer basic Physics of the Physics Learning Achievement. The population in this study were all students IPA of the Department of Education consists of 209 students. This study is a population study. To collect data on value leadership lecturer used Likert scale questionnaire listing, The collect data on the basic physics lab values and the value of basic physics is through a written test and skills. For the processing of the data used multiple correlation coefficient formula. Based on the results of processing and analysis of data obtained can be concluded that: There is influence between leadership and ability Lecturer Basic Physics Lab of learning achievement student force in 2006 in the course of Basic Physics.